PENGARUH LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN, DAN PERPUTARAN TOTAL ASET TERHADAP PROFITABILITAS - Chelsea Adria, Liana Susanto (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to know the effect leverage, liquidity, firmsize, and total assets turnover on firm profitability on manufacturing company listed in BEI from 2015-2017. This research used 165 observations that were selected using purposive sampling methodin three years. This research uses SPSS software version 21 to analyse the hypothesis. The result for this research showed that there is a positive and significant effect of leverage, liquidity, firm size, and total assets turnover on firm profitability.